A felnőttképzés jellemzői. 1. rész : a képzés és fejlesztés "házon kívüli" módszerei - Gulyás, László (Közép-Európai Közlemények, 2014)
The knowledge-based society and economy has a new demands írom employee. The long life leaming is becoming reality. Where upon the theory and practice of training and development is growing day after day. HR-managers, HR-specialist and researchers produced several models and methods of training and development. There can be sorted two big groups: 1. On the job methods2. Off the job methodsRecent essay is dealing with the theory of “off the job” methods. Accordingly we review the Hungárián HR-books and essays dealing with “on the job” methods. We examine the advantages and disadvantages of different methods, sort and evaluate them.